THE APPLICATION EQ AND SQ IN LEARNING MATHEMATICS WITH BRAIN-BASED LEARNING APPROACH TO IMPROVE STUDENTS’ MATHEMATICAL CONNECTION AND SELF-EFFICACY IN SENIOR HIGH SCHOOL - Hakim, Luki Luqmanul; Cahya, Endang; Nurlaelah, Elah; Lestari, Zubaedah Wiji (PEOPLE: International Journal of Social Sciences, 2015)
In this study, placing EQ and SQ in addition to IQ as learning objectives is based on current situation, that previously IQ is considered as the intelligence that strongly support students’ success in learning. Nowadays, it was realized that there are other intelligences that equally important which can support the success of learning process, those are EQ and SQ. Implementing EQ and SQ in learning hopefully influence students’ cognitive and psychology. Therefore, this study aims to identify the improvement of students’ mathematical connection skills and self-efficacy that experience Brain-Based Learning approach that apply EQ and SQ compare to students who experience conventional learning, both in terms of overall students as well as Mathematics Initia lAbility. This study applies quasi-experimental research with Non-equivalent Control Group Design. The subjects in this research are 68 students of the 11th grade at senior high school, which consists of 34 students as the experimental class and 34 as the control class. The experimental class experience Brain-Based Learning approaches that apply EQ and SQ, whereas the control class experience conventional learning. In this research, to obtain the data the writer use instruments such as mathematical connection skills tests and self-efficacy scale. Based on the results of the data analysis it can be concluded that the increase of students’ mathematical connection skills and self-efficacy who experience Brain-Based Learning approach that apply EQ and SQ are better than students who received conventional learning, both in terms of overall students as well as the Mathematics Initial Aability.